Impact of Teacher Competency and Teaching Methods on Clothing and Textiles Learning among Home Economics Students in Colleges of Education in Delta and Anambra States, Nigeria - Deborah Chibuzor Abamba; Juliana Ego Azonuche; Oghenetega Ichekor; May Uzoma Egodike (Jurnal Indonesia Pendidikan Profesi Guru, 2024)
Objective: This study investigates the impact of teacher competency and teaching methods on Clothing and Textiles learning among Home Economics students in Colleges of Education in Delta and Anambra States, Nigeria. It also explores potential regional disparities in teacher training and resource allocation. Method: The study adopted a census approach, utilizing the entire population of 361 Home Economics students across selected institutions. Data were collected through structured questionnaires. Descriptive statistics (mean and standard deviation) were used for data analysis, while hypotheses were tested using the Pearson Product Moment Correlation at a 0.05 significance level. Result: The findings revealed a significant relationship between teachers' competence and students' subject preference. Additionally, a significant relationship was found between the teaching methods adopted and student learning in Clothing and Textiles. Conclusion: The results indicate that teacher competency and the teaching methods significantly affect students' engagement and learning outcomes in Clothing and Textiles. Contribution: The study offers valuable insights for educators, policymakers, and academic administrators seeking to improve the quality of Home Economics education. It recommends the engagement of qualified personnel and the adoption of effective methodologies to enhance teaching and learning in the subject area.